2018
DOI: 10.1556/038.53.2018.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc oxide nanoparticles (ZnO NPs) and some plant pathogens on the growth and nodulation of lentil (Lens culinaris Medik.)

Abstract: Effects of ZnO nanoparticles (NPs) were studied on lentil plants inoculated with Alternaria alternata, Fusarium oxysporum f. sp. lentis, Xanthomonas axonopodis pv. phaseoli, Pseudomonas syringae pv. syringae and Meloidogyne incognita. Plant growth, chlorophyll, carotenoid contents, nitrate reductase (NR) activity and nodulation of lentil both in the presence and absence of Rhizobium sp. were examined in a pot test. Inoculation of plants with A. alternata / F. oxysporum f. sp. lentis / X. axonopodis pv. phaseol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Several studies have evaluated NP effects on lentil production. These include biosynthesized Au-NPs [ 57 ], SiO 2 -NPs [ 58 ], TiO 2 -NPs [ 59 ], ZnO-NPs [ 60 ] and Ag-NPs [ 61 ]. The studies, however, do not consider the changes in content of nutrients such as minerals which affect final lentil seed quality.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have evaluated NP effects on lentil production. These include biosynthesized Au-NPs [ 57 ], SiO 2 -NPs [ 58 ], TiO 2 -NPs [ 59 ], ZnO-NPs [ 60 ] and Ag-NPs [ 61 ]. The studies, however, do not consider the changes in content of nutrients such as minerals which affect final lentil seed quality.…”
Section: Resultsmentioning
confidence: 99%
“…Taheri et al (2015) found that all the three helps in improving shoot dry matter and leaf area index while the best result given by ZnO nanoparticle treatment so they concluded that zinc nanoparticles can improve corn growth and yield in mineral-depleted soils. Siddiqui et al (2018) reported that a foliar spray of ZnO NPs to plants lacking Rhizobium resulted in significant improvements in lentil growth, pod number, chlorophyll, carotenoid content, and NR activity in both inoculated and uninoculated plants. Thunugunta et al (2018) observed positive impact of ZnO nanoparticles to the seedling growth of eggplant under greenhouse conditions while negative impact has been seen under tissue condition.…”
Section: (Ii) Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…oryzae ) [ 81 ], tomato bacterial spot pathogen (copper-tolerant strains of Xanthomonas perforans ) [ 117 ], the causative agent of lentil bacterial leaf spot ( Xanthomonas axonopodis pv. phaseoli ) [ 118 ], the causative agent of bacterial blight of lentil ( Pseudomonas syringae pv. syringae ) [ 118 ], and eggplant bacterial wilt pathogen ( Ralstonia solanacearum ) [ 119 ].…”
Section: Zinc Nanomaterials and Their Use For Curbing Plant Diseasmentioning
confidence: 99%
“…phaseoli ) [ 118 ], the causative agent of bacterial blight of lentil ( Pseudomonas syringae pv. syringae ) [ 118 ], and eggplant bacterial wilt pathogen ( Ralstonia solanacearum ) [ 119 ].…”
Section: Zinc Nanomaterials and Their Use For Curbing Plant Diseasmentioning
confidence: 99%